Mitigation of flow instabilities in multiport minichannel thermosyphon through a modified loop design with separate vapor-liquid paths - Jaya Antony Perinba Selvin Raj; Lazarus Godson Asirvatham; Appadurai Anitha Angeline; Bairi Levi Rakshith; Jefferson Raja Bose; Stephen Manova; Vivek Vengatoor Mana; Mostafa Safdari Shadloo; Somchai Wongwises (Case Studies in Thermal Engineering)
Multiport minichannel thermosyphons with hydraulic diameters below 1.2 mm often encounter severe flow instabilities and oscillations in vapor and condensate movement, which hinder effective phase change processes. These instabilities can cause partial and localized dry-out, resulting in higher operating temperatures and reduced thermal performance. To overcome these limitations, a novel multiport minichannel thermosyphon loop (MPMCTSL) is proposed. This design integrates a compensation chamber (CC) to ensure uniform fluid distribution across all channels and suppress instabilities near the evaporator. Additionally, the loop features separate flow paths for vapor and liquid to mitigate entrainment issues. The study experimentally investigates the thermal performance of MPMCTSL using acetone as the working fluid, considering fill ratios of 40 %, 50 %, and 60 %, inclination angles of 0°, 30°, 60°, and 90°, and varying heat loads from 10 to 80 W. Results demonstrate that 5 mm CC length delivers optimal performance by stabilizing condensate flow and ensuring continuous fluid replenishment to the evaporator. This results in minimum thermal resistance of 0.34 K/W and a peak vapor velocity of 4.36 m/s at 80 W heat load. Furthermore, the observed flow regime transition from churn to annular with increasing heat input confirms the improved stability and effectiveness of the MPMCTSL design.